Dissecting genomes of multiple yak populations: unveiling ancestry and high-altitude adaptation through whole-genome resequencing analysis - Sheikh Firdous Ahmad; Munish Gangwar; Amit Kumar; Amod Kumar; Mahesh Shivanand Dige; Girish Kumar Jha; Gyanendra Kumar Gaur; Triveni Dutt (BMC Genomics)
Abstract The present study was undertaken to elucidate the population structure and differentiation of Indian yak from Chinese and wild cohorts on genome-wide scale by identifying the selection sweeps and genomic basis of their adaptation across different comparisons while analyzing whole genome sequencing (WGS) data using latest bioinformatics tools. The study included 105 individuals from three distinct yak populations i.e., Indian yak (n = 29); Chinese yak (n = 61) and wild yak (n = 15), hypothesized to be related along the evolutionary timescale. Efficient variant calling and quality control in GATK and PLINK programs resulted in around 1 million (1,002,970) high-quality (LD-independent) SNPs with an average genotyping rate of 96.55%. The PCA, ADMIXTURE and TREEMIX analysis revealed stratification of the yak groups into three distinct clusters. The empirical distribution pattern of minor allele frequency (MAF) of SNPs on genome-wide scale was also elucidated for three yak cohorts revealing unique distribution across five different bins. The selection signature analysis revealed candidate genes that are important for the adaptation of Indian yak against harsh environmental conditions in their habitats. Under iHS analysis, several genes were identified to be under selection pressure in Indian yak including ABCA12, EXOC1, JUNB, KLF1, PRDX2, NANOS3, RFX1, RFX2, and CACNG7. On the other hand, across population analysis revealed the genes like NR2F2, OSBPL10, CIDEC, WFIKKN2, ADCY, THSD7A, ADGRB3, TRPC1, VASH2, and ABHD5 to be part of selective sweeps under these comparisons. A total of 53 genes were found common between intra- and inter-population selection signature analysis of Indian yak. Notably, the genes harbouring the SNPs under selection pressure were significant for adaptation traits including lipidogenesis, energy metabolism, thermogenesis, hair follicle formation, oxidation–reduction reactions, hypoxia and reproduction. These genes may be evaluated as candidate genes for livestock adaptation to harsh environmental conditions and to further the research and application in the present era of climate change.